Integrating UAV-based flight control systems into OMNet++ through socket connections - Rohan Jain. (2011)
The project aims at developing the flight control system of a group of Unmanned Aerial Vehicles (UAVs) for various purposes such as navigation, search and rescue and reconnaissance or even to provide a telescopic eye for the Unmanned Ground Vehicle (UGV). The cooperative multi-robot system shares information or tasks to accomplish common solo or series objectives. This brings several advantages over single robot approach and greater efficiency and operational capabilities can be realized from a team of vehicles operating in a coordinated fashion. The robustness of the system increases as well with redundant capabilities and dynamically reconfiguring the team in case of robot failures.